2021
DOI: 10.1371/journal.pone.0258431
|View full text |Cite|
|
Sign up to set email alerts
|

Diet impacts on the biological aspects of pink bollworm, Pectinophora gossypiella (Lepidoptera: Gelechiidae) under controlled laboratory conditions

Abstract: Background Pink bollworm, Pectinophora gossypiella (Lepidoptera: Gelechiidae) is a native pest of Asia and preferably invasion on cotton (Gossypium hirsutum L.) crop as a commendatory host plant. Commercially, G. hirsutum is known as white gold and is an important cash crop all over the globe. Limited studies were published to focus on certain dietary compositions against different cotton pests. Therefore, the present study was undertaken in the laboratory under controlled conditions (temperature: 27 ± 2°C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…The biology/fitness of P. gossypiella has been covered on various natural host plants and cotton, corn and wheat based artificial diets using old/simple table analysis in a number of studies 28 , 33 – 35 . When study the biology of an insect on artificial diet as compared to growing on natural food, feeding promote fitness reduces the amount of work, time, space, and money needed to cultivate the host plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biology/fitness of P. gossypiella has been covered on various natural host plants and cotton, corn and wheat based artificial diets using old/simple table analysis in a number of studies 28 , 33 – 35 . When study the biology of an insect on artificial diet as compared to growing on natural food, feeding promote fitness reduces the amount of work, time, space, and money needed to cultivate the host plants.…”
Section: Discussionmentioning
confidence: 99%
“…The larval duration of P. gossypiella was in the range of 18–21 days on a chickpea flour- and wheat-gram-based diet 28 . However, in another study it was reported that the average larval duration of P. gossypiella was 25 days on an artificial diet 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pest has a restricted host range with cotton (Gossypium spp.) as the most preferred host, followed by okra (Hibiscus esculentus L.); alternatively the pest also thrives on almost 70 species distributed across seven families in 24 plant genera (Ihsan et al, 2021). The adult female moth preferably lays her eggs on tender leaves, squares and flower buds, singly or in small groups.…”
Section: Introductionmentioning
confidence: 99%
“…The PLOS ONE Editors retract this article [ 1 ] because it was identified as one of a series of submissions for which we have concerns about authorship, competing interests, and peer review. We regret that the issues were not addressed prior to the article’s publication.…”
mentioning
confidence: 99%